Improved fatigue resistance of gradient nanograined Cu. (March 2019) - Long, Jianzhou; Pan, Qingsong; Tao, Nairong; Dao, Ming; Suresh, Subra; Lu, Lei
Abstract: Cyclic stresses generally lead to fatigue damage and failure with important implications for material and component design, safety, performance and lifetime costs in major structural applications. Here we present unique results for copper to demonstrate that a thin superficial layer of graded surface nanostructure over a coarse-grained core suppresses strain localization and surface roughening, thereby imparting unprecedented resistance to both low-cycle and high-cycle fatigue without compromising ductility. Progressive homogenization of the surface-graded copper is shown to be superior in fatigue properties compared to that of any of its homogeneous counterparts with micro-, submicro- or nano-grained structures. Since the findings here for enhancing resistance to fatigue are broadly applicable to a wide spectrum of engineering metals and alloys, the present results offer unique pathways to mitigate fatigue damage using a broad variety of processing routes, geometric design considerations, and structural parameters in many practical applications. Graphical abstract: Image 1